Det’ lig’som teksten sådan bølger: Forfatterskolens æstetiske og undersøgende tekstlæsninger som inspiration til gymnasiets klassesamtaler om litteratur - Bang, Louise Rosendal (Passage - Tidsskrift for litteratur og kritik, 2020)
This article addresses the practice of shared readings at The Danish Academy of Creative Writing. It argues that these readings represent exploratory talk as a method of reading the aesthetic dimensions of literary texts. Moreover, it points out that both exploratory approaches and aesthetic readings are of increasing interest within the field of didactical research. The article aims to investigate the shared readings at the Danish Academy of Creative Writing as a supplement to the highly analytical classroom conversations about literature in Danish high schools.